Fermi LAT Discovery of Extended Gamma-Ray Emission in the Direction of Supernova Remnant W51C - Abdo, A.; Ackermann, M.; Ajello, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Baring, M.; Bastieri, D.; Baughman, B.; Bechtol, K.; Bellazzini, R.; Berenji, B.; et al. (Institute of Physics Publishing, 2009)
The discovery of bright gamma-ray emission coincident with supernova remnant (SNR) W51C is reported using the Large Area Telescope (LAT) onboard the Fermi Gamma-ray Space Telescope. W51C is a middle-aged remnant (~104 yr) with intense radio synchrotron emission in its shell and known to be interacting with a molecular cloud. The gamma-ray emission is spatially extended, broadly consistent with the radio and X-ray extent of SNR W51C. The energy spectrum in the 0.2-50 GeV band exhibits steepening toward high energies. The luminosity is greater than 1 × 1036 erg s-1 given the distance constraint of D > 5.5 kpc, which makes this object one of the most luminous gamma-ray sources in our Galaxy. The observed gamma-rays can be explained reasonably by a combination of efficient acceleration of nuclear cosmic rays at supernova shocks and shock-cloud interactions. The decay of neutral pi mesons produced in hadronic collisions provides a plausible explanation for the gamma-ray emission. The product of the average gas density and the total energy content of the accelerated protons amounts to \bar{n}_HW_p ~= 5× 10^{51} (D/6 kpc)^2 erg cm^{-3}. Electron density constraints from the radio and X-ray bands render it difficult to explain the LAT signal as due to inverse Compton scattering. The Fermi LAT source coincident with SNR W51C sheds new light on the origin of Galactic cosmic rays.